Pengaruh Pemahaman Investasi, Risk Tolerance, Dan Overconfidence Terhadap Minat Berinvestasi Di Pasar Modal Dengan Kemajuan Teknologi Sebagai Variabel Moderasi - Irawan, Daffa; Suyanto, Suyanto; Retnaning Rahayu, Sri (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to analyze the effect of Investment Understanding, Risk Tolerance, and Overconfidence on Investment Interest in the Capital Market with Technological Advancement as a Moderating Variable in students of the Faculty of Economics and Business, Muhammadiyah University of Metro. The type of research used in this study is quantitative. The Sample used in this study are 304 respondents are obtained. The results of this study indicate that Investment Understanding affects Interest in Investing in the Capital Market, Risk Tolerance does not affect Interest in Investing in the Capital Market, and Overconfidence affects Interest in Investing in the Capital Market. Then in the Moderated Regression Analysis test, the results obtained were that Technological Progress moderates Investment Understanding on Interest in Investing in the Capital Market, Technological Progress does not moderate Risk Tolerance on Interest in Investing in the Capital Market, and Technological Progress moderates Overconfidence on Interest in Investing in the Capital Market.